(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the current state of formation of the student’s ecological thinking in the teaching of "Natural Science" in the 4th grade, the study of the scientific literary heritage of Central Asian thinkers and their views on the relationship of man to the ecological environment covered in them, the knowledge of nature in preschool children based on mass media formation technologies are described in detail.